Mathematical modelling of thin layer drying of pear - Lutovska Monika; Mitrevski Vangelce; Pavkov Ivan; Mijakovski Vladimir; Radojčin Milivoj (Chemical Industry and Chemical Engineering Quarterly, 2016)
In this study, a thin - layer drying of pear slices as a function of drying conditions were examined. The experimental data set of thin - layer drying kinetics at five drying air temperatures 30, 40, 50, 60 and 70°C, and three drying air velocities 1, 1.5 and 2 m s-1 were obtained on the experimental setup, designed to imitate industrial convective dryer. Five well known thin - layer drying models from scientific literature were used to approximate the experimental data in terms of moisture ratio. In order to find which model gives the best results, numerical experiments were made. For each model and data set, the statistical performance index, (φ), and chi-squared, (χ2), value were calculated and models were ranked afterwards. The performed statistical analysis shows that the model of Midilli gives the best statistical results. Because the effect of drying air temperature and drying air velocity on the empirical parameters was not included in the base Midilli model, in this study the generalized form of this model was developed. With this model, the drying kinetic data of pear slices can be approximated with high accuracy. The effective moisture diffusivity was determined by using Fick’s second laws. The obtained values of the effective moisture diffusivity, (Deff), during drying ranged between 6.49 x 10-9 and 3.29 x 10-8 m2 s-1, while the values of activation energy (E0) varied between 28.15 to 30.51 kJ mol-1.